PENGARUH BUAH KURMA TERHADAP KEMAJUAN PERSALINAN (Jurnal Kesehatan Siliwangi, 2022)
Labor is a physiological process that requires stamina and excellent body condition because the body's metabolism increases due to the body's muscle activities and anxiety. The body's muscle activities when the mother is ladies need optimal energy. One of the nutrients that can be consumed is dates, research shows date fruit (Dactilifera Phoenix) has a good nutritional content for the body, rich in carbohydrates, vitamins and other minerals. The purpose of this journal study is to find out the effect of giving date fruit on the progress of labor. E-Data based search method with Pubmed data source and Garuda Portal with vulnerable time 2016-2021 using keywords Date fruit, phoenix dactylifera Linn, Kurma, Labor progress, Delivery with boolean operator "OR" and "AND”. The results of the overall journal review are that there is an influence on the administration of date fruit on the progress of labor. It was concluded that date fruit has an influence on the progress of labor, but this may also occur in patients due to other supporting factors. So the need to strengthen knowledge about the benefits and effects of the consumption of date fruit and reduce the risk factors bias to the critical review of the journal. It is hoped that researchers can further find out the exact dose of giving dates using effective methods or tools to reduce the risk of bias, considering the weight of each date is different.